PEMBENTUKAN KARAKTER AKHLAKUL KARIMAH MELALUI METODE USWATUN HASANAH - Hammam Hammam; Hairul Huda (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2023)
This study aims to determine the effect of the application of the Uswatun Hasanah method in shaping the character of the 8th grade students of Mts Imam Syafii Genteng Banyuwangi who have good morals. In this study the subjects were grade 8 students, totaling 25 students, all of whom were boys. In this study, the researchers designed using PTK (Classroom Action Research) with 4 stages, namely (1) Planning (2) Implementation (3) Observation, and (4) Reflection. For data collection techniques, here researchers use evaluation or tests. There is an increase in the percentage of student completeness that occurs in the results of research on students' moral character. This can be seen in the actions from cycle I to cycle II which showed an increase. Because in Cycle I the results achieved were 32% of students who achieved good and very good indicators, the remaining 68% were still in sufficient and insufficient. Whereas in Cycle II it increased to 92% of students on good and very good indicators, and the remaining 8% were on less indicators. This research has been able to improve the character of akhlakul karimah in grade 8 students of MTs Imam Syafii Genteng Banyuwangi Regency.